2010
DOI: 10.1002/bip.21428
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of lovastatin and related metabolites formed by fungal iterative PKS enzymes

Abstract: The fungal polyketide lovastatin is a cholesterol lowering agent that is an immediate precursor to a multi‐billion dollar drug, simvastatin (Zocor™). Lovastatin is produced by an iterative type I polyketide synthase known as LovB and a partner enoyl reductase (LovC). There is evidence that a Diels‐Alderase enzyme activity is utilized in its biosynthesis. This review examines the biosynthesis of lovastatin, as well as of compactin, equisetin, cytochalasins, and solanapyrones, which are other structurally relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
65
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 66 publications
0
65
0
2
Order By: Relevance
“…Polyketides comprises diverse fungal secondary metabolites such as antibiotics, pigments, and mycotoxins that are formed from simple carbon precursor acids catalyzed by polyketide synthases (PKSs) [57]. Filamentous fungi are producers of polyketide metabolites, several of which of pharmacological or agricultural interest [58, 59]. Fungal PKSs are in general a linear succession of ketosynthetase (KS), acyltransferase (AT), dehydratase (DH), enoyl reductase (ER), ketoreductase (KR), acyl carrier protein (ACP), and thioesterase (TE) domains [60].…”
Section: Resultsmentioning
confidence: 99%
“…Polyketides comprises diverse fungal secondary metabolites such as antibiotics, pigments, and mycotoxins that are formed from simple carbon precursor acids catalyzed by polyketide synthases (PKSs) [57]. Filamentous fungi are producers of polyketide metabolites, several of which of pharmacological or agricultural interest [58, 59]. Fungal PKSs are in general a linear succession of ketosynthetase (KS), acyltransferase (AT), dehydratase (DH), enoyl reductase (ER), ketoreductase (KR), acyl carrier protein (ACP), and thioesterase (TE) domains [60].…”
Section: Resultsmentioning
confidence: 99%
“…The structural similarity of 1 , 2 and lovastatin 3 suggested that the decalin core of 1 may be formed by an intramolecular DA reaction, as proposed for the biocatalytic formation of the decalin cores of 2 and 3 (Figure 1B). [12] To gain further insight into the mechanism of biosynthesis of 1 and to determine if a DA reaction is indeed involved in the biosynthesis of 1 , we identified the C. globosum gene cluster responsible for the biosynthesis of 1 for a detailed investigation.…”
mentioning
confidence: 99%
“…In a fungal context, it is a compound that blocks the first step of the terpene biosynthesis for the production of ergosterol (the main component of cell membranes in fungi). It was first discovered in Aspergillus terreus and is a precursor of other successful anti-cholesterol drugs [45]. However, the antifungal properties of some statins have been known for years and recent studies have shown that statins bring to bear relevant antifungal effects against dermatophyte fungi and, in combination with other clinically used antifungal agents, can significantly improve the treatment using combined therapy [46].…”
Section: Resultsmentioning
confidence: 99%